China and India, 2025 A Comparative Assessment - Wolf, Jr (RAND Corporation, 2011)
China and India, the world's two most populous countries, will exercise increasing influence in international affairs in the coming decades. This document assesses the relative prospects of China and India through 2025 in four domains: demography, macroeconomics, science and technology, and defense spending and procurement. In each domain, the authors try to answer the following questions: Who is ahead? By how much? and Why?